Impact of bio-mimetic cilia and symmetry breaking wave on double-diffusive radiated magneto Cu-Al2O3/bloodstream in an electroosmotic pump under momentum-thermal slip constraint - Munawar, Sufian; Saleem, Najma; Mehmood, Ahmer (Waves in random and complex media, 2022)
Transport of drug/hybrid materials through microfluidic channels requires efficient flow capability, effective mixing, and manipulation. To address this subject, a thermal analysis of double-diffusive stream of hybrid-type radiated bloodstream is considered through an elastic electroosmotic micropump in the presence of a magnetic field. Bio-mimetic cilia are embedded inside the pump surface having momentum-thermal slip effects. The inserted cilia strike and a constant phase difference between the beats of adjacent cilia generate a set of symmetry-breaking metachronal waves along the pump surface. The deemed mathematical model is simplified under the Debye-Hückel linearization and lubrication approach and is solved numerically. The analysis shows that the wall asymmetry and the apt cilia length strengthen the fluid stream and ensure active mixing distributed across significant distances. The radiated blood, the thin EDL, and extended cilia may be regarded as key factors in the cooling process. The entropy formation inside the micropump can be curtailed with the provision of an adequate amount of activation energy and the consideration of velocity-thermal slip effects on the ciliated surface. The intended model may deliver a deep perception of the thermal design of a futuristic drug delivery pump for efficient flow, adequate mixing, and least entropy generation.